2019
DOI: 10.1136/bmjsem-2019-000529
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of lumbar stress fracture in English County Cricket fast bowlers, association with bowling workload and seasonal variation

Abstract: ObjectivesSince much of the previous epidemiological research into lumbar stress fracture was conducted, there has been a marked increase in the amount of cricket being played. The aims were to determine the incidence and prevalence of lumbar stress fracture in English County Cricket fast bowlers between 2010 and 2016, determine the association with match bowling workload and observe seasonal variation in workload and injury.MethodsLumbar stress fracture incidence and prevalence rates were calculated using new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…2 Efforts to reduce injury rates in this population have led to investigations of the influence of bowling volumes and bowling session frequency on injury risk. 3 Several authors have reported both high and low bowling loads to be associated with increased injury, 4,5 and recommendations for 'safe' fast bowling volumes/frequencies have been proposed. 6 Following on from these initial load-injury investigations in cricket, the ratio of acute (one-week) to chronic (four-week rolling average) loads have been modelled against injury risk, with this metric termed the 'acute-to-chronic workload ratio' (ACWR).…”
Section: Introductionmentioning
confidence: 99%
“…2 Efforts to reduce injury rates in this population have led to investigations of the influence of bowling volumes and bowling session frequency on injury risk. 3 Several authors have reported both high and low bowling loads to be associated with increased injury, 4,5 and recommendations for 'safe' fast bowling volumes/frequencies have been proposed. 6 Following on from these initial load-injury investigations in cricket, the ratio of acute (one-week) to chronic (four-week rolling average) loads have been modelled against injury risk, with this metric termed the 'acute-to-chronic workload ratio' (ACWR).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of lumbar stress fracture (LSF) is high in fast bowlers, with up to 67% having a history of LSF across their career (Johnson et al, 2012). LSF are most prevalent at the fourth and fifth lumbar vertebra (66% of all incidence), with 93% of all LSF occuring at the neural arch on the non-dominant side (contralateral to bowling arm, Alway et al, 2019). This unilateral injury may be a result of the increased stress placed on this area, with a finite element analysis estimating that stresses within the neural arch on the nondominant side of L4 are up to 10% greater than on the dominant side (De Visser et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fast bowlers with stress fractures could be a subset of cricketers to focus on for any proposed intervention, given the relative availability of research in this area and well documented recovery phases. 1 46 47 …”
Section: Discussionmentioning
confidence: 99%
“…Injury epidemiology reporting within the cricket medical literature has emerged over the past 2 years with a focus on physical injuries. [1][2][3][4] Cricket researchers have been proactive in standardising the description of physical injuries in order to better define injury cohorts and structure appropriate preventive and responsive services. 5 6 In contrast, there is a lack of research evidence on the mental health of cricketers, despite this being an area of interest within the wider sporting medical literature.…”
Section: Introductionmentioning
confidence: 99%